Opening Lines of Communication With E-mail - Blackerby, John Michael Jr (My University, 2004)
The purpose of the research was to determine the impact of promoting school communication via e-mail on parents' attitude and practices of communicating with the school. Throughout the intervention, parents were given the opportunity and encouraged to use e-mail as an alternate means of school communication. The study was directed towards parents in kindergarten through fifth grade students at the targeted school. The parents were initially surveyed to determine their preferences in communicating with the school. The intervention group consisted of 146 families that voluntarily supplied an e-mail address to the school. Throughout the intervention, parents were encouraged to use e-mail to communicate with the school. A running record of all types of parent communication was kept during the intervention the period. A post intervention survey on parent e-mail use was given to the families. Results from the study indicate that parents feel that they initiate most school communication. Among all parents, telephone calls, written communication, and school visits were the preferred primary means of communication. However, the majority of parents in the intervention group indicated they would use e-mail as a means of communicating with the school. The results of the study were communicated to the learning community during a faculty meeting at the school. Further exploration of the e-mail communication program will continue through the efforts of the school leadership team.
Keywords: Communication; E-mail; Running record